La protection de la jeunesse comme légitimation du contrôle des médias - Jean-Matthieu Méon (Amnis)
This paper proposes a comparative analysis of the systems created in France and in the United States after the Second World War in order to control the content of youth publications. It presents the mobilizations that denounced the danger of “demoralizing” and “crime-inducing” publications and the diversity of the systems thus created – public control in France, private control in the United States. So, this paper emphasises the importance of the discourses about the “protection of youth” as a way to legitimise media control. The comparative approach demonstrates as well how authorities / medias relationships must be considered in their historical, national, social and political contexts.